Ecotourism, wildlife conservation, and agriculture in Costa Rica through a social-ecological systems lens - Miller, Anna B.; Cox, Cody; Morse, Wayde C. (Frontiers in Sustainable Tourism, 2023)
Parks and protected areas have long been promoted for their environmental conservation benefits, opportunities for outdoor recreation and nature-based tourism, and associated economic opportunities. However, conservation biologists and ecologists are increasingly embracing the idea that achieving their conservation goals requires working outside these protected areas and within more developed agricultural lands occupied and used by people. This shift toward a systems perspective for conservation involves working within integrated social and ecological systems. Outdoor recreation and nature-based tourism operate within these same linked systems across a range of scales. Ecotourism in particular is a complex social-ecological system (SES) that relies on environmental resources such as protected areas, tourism industry elements such as lodging and transportation, and locals who obtain their livelihoods in the surrounding regions. To understand this complex system, we apply a framework for situating disciplines within an SES across scales. This framework includes two-way interactions between nested hierarchical levels of social and ecological systems. Interactions range from positive to negative, forming a four-quadrant framework. We argue that this framework is more representative of this highly complex system of ecotourism than traditional human-impact research and provides a more holistic understanding of the nature-based recreation ecosystem. We apply this SES to a case study in Costa Rica, where ecotourism has become an important source of income for residents and thus generates conservation success. Our study area comprised the upper Guacimal watershed, a regional tourism hub in northwestern Costa Rica. We apply this SES framework to interview data regarding missions, goals, and management practices from representatives of 20 government and non-government organizations active in conservation, and thus engaged in ecotourism, in the area. Applying our SES framework to the Costa Rican case study revealed the dimension of varied challenges and benefits of ecotourism for and by local conservation organizations as compared with ecotourist visitors. The framework reveals opportunities for identifying trade-offs and maximizing benefits to social and ecological systems while minimizing negative impacts. Through this framework, we also discuss how ecotourism can contribute toward conservation of unregulated lands. Considering ecotourism as an SES can enable more comprehensive decision-making around an ecotourism system.